THE SOLAR RENEWABLE ENERGY SYSTEM STUDY WITH A CAPACITY OF 1300 W UTILITIZING POLYCRYSTALLINE PHOTOVOLTAIC - Armin Sofijan (Journal of Mechanical Science and Engineering, 2019)
Abstract—Solar energy is one of the alternative energy that is environmentally friendly and cheap raw materials and available throughout the year as a substitute for conventional energy whose raw materials are getting thinner and have a bad impact on the environment such as air pollution, noise and hazardous waste for the environment over a long period of time, solar energy has great potential as an independent solar power plant, which offers solutions to provide electricity to meet electricity needs, especially in areas not yet covered by the electricity grid of the National Electric Company. The 1300 W solar power plant is planned to use polycrystalline solar panels with a capacity 100 WP, combined with battery components and inverters, it can generate AC current for daily electricity needs. The greater the electrical load, the faster the battery life. This research shows that it takes 60 polycrystalline solar panels for 12 hours, 26 Solar Chargers 15 A, 9 batteries with a capacity of 150 Ah, and 15 Inverters 1300 W